TRANSFORMATION OF FAMILY SHAPE POST EARTHQUAKE AL-FARUQI'S 'AILAH LAMYA' THEORY PERSPECTIVE - Nanang Syaggap Armanda; Hawa’ Hidayatul Hikmiyah (CV. Fahr Publishing, 2023)
Changes to a small family continued until the earthquake in Lombok occurred. The Lombok earthquake that occurred in the East Lombok and North Lombok regions had a huge impact. The impact is also felt by all people of Lombok. One of them is the Banjar village community. This study aims to reveal What are the factors that have caused a change in the shape of the family after the earthquake in Kampung Banjar Mataram, and What is the perspective of the theory of 'ailah Lamya' al-Faruqi on the factors that caused a change in the form of kinship after the earthquake in the Banjar village of Mataram. This research uses a qualitative approach. Data collection is done by interview and documentation techniques. The data analysis technique starts with checking the validity of the data, presenting the data, analyzing the theory of 'the God of Lamya' al-Faruqi and drawing conclusions. The results showed: 1). Existing factors will be divided into 2 sub sections, namely as follows: first, external factors are factors that originate from outside, such as: family environment, the surrounding environment and natural conditions. Based on the results of all the interviews we will find that the Lombok earthquake is an external factor in the form of natural conditions that cause changes in the form of kinship to the people of Kampung Banjar. Second, internal factors are derived from human personality and awareness. This can be known through human awareness of several things that he has forgotten or not maintained, especially in terms of maintaining relationships with extended families. 2). This, if observed with theory, is that this will affect the role later. The existing role influences the form in the family and ends in a better family culture and forms a family culture that is applied in all layers of the banjar village community. The form of a large family formed in the banjar village community is a functional family extended (functionally extended). Keywords: Family System, Post-Earthquake, ‘Ailah Lamya’ Al-Faruqi